2014
DOI: 10.1657/1938-4246-46.4.767
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Hurricane Disturbance in a Tropical Montane Forest Landscape in the Cordillera Central, Dominican Republic: Implications for Vegetation Patterns and Dynamics

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(58 citation statements)
references
References 46 publications
2
55
0
1
Order By: Relevance
“…Future work is needed to better understand the effects of both natural and human disturbance on patterns of Caribbean SDTF composition. Hurricanes are an important natural disturbance in the Caribbean (Mumby, Vitolo, & Stephenson, ) driving forest dynamics (Gannon & Martin, ; Tanner, Rodriguez‐Sanchez, Healey, Holdaway, & Bellingham, ), whereas continental Neotropical SDTF experiences fewer hurricanes on average (Bullock, Mooney, & Medina, ). Human disturbance includes forest clearing (Chazdon, ) and selective tree removal (Murphy & Lugo, ).…”
Section: Discussionmentioning
confidence: 99%
“…Future work is needed to better understand the effects of both natural and human disturbance on patterns of Caribbean SDTF composition. Hurricanes are an important natural disturbance in the Caribbean (Mumby, Vitolo, & Stephenson, ) driving forest dynamics (Gannon & Martin, ; Tanner, Rodriguez‐Sanchez, Healey, Holdaway, & Bellingham, ), whereas continental Neotropical SDTF experiences fewer hurricanes on average (Bullock, Mooney, & Medina, ). Human disturbance includes forest clearing (Chazdon, ) and selective tree removal (Murphy & Lugo, ).…”
Section: Discussionmentioning
confidence: 99%
“…TMFs also have few to no lianas which can make gaps much larger in lowland forests by bringing down neighbouring trees when a tree falls (Grubb 1977, Putz 1984). Finally, when trees do fall in a TMF, they frequently survive partially or fully horizontal (Gannon & Martin 2014, Soethe et al . 2006), further limiting the opening in growing space created by the gap.…”
Section: Disturbance Regimes In Tropical Montane Forestsmentioning
confidence: 99%
“…
Figure 4. Linear regression and 95% confidence intervals between cyclone return intervals and degrees of latitude (north or south) based on data reported in published papers from tropical montane forests from northeastern Mexico (Arriaga 2000), Mexico and Guatemala (Vargas-Rodriguez & Platt 2012), Puerto Rico (Walker et al . 1996), Dominican Republic (Gannon & Martin 2014), Jamaica (Bellingham et al . 1995) and Australia (Herwitz & Young 1994).
…”
Section: Disturbance Regimes In Tropical Montane Forestsmentioning
confidence: 99%
“…The causes of the ecotone at 2200 m, however, are not as clear-it appears to form due to a complex set of interactions where climate plays a more indirect role on vegetation through its influence on the fire regime, controlling how low fires are likely to extend. Frequent clouds at 2100 m prevent most fires (which usually occur in the dry season; Martin and Fahey, 2006) from burning lower than 2200 m. Indeed, the scarcity of fire in this zone is evident in the near complete absence of Pinus occidentalis in the cloud forest (Gannon and Martin, 2014). Direct observations of the behavior of a severe fire also indicated that it soon extinguished as it entered the cloud forest vegetation from the pine forest above (Sherman et al 2008).…”
Section: Climate and Forest Zonation Patternsmentioning
confidence: 99%